Dominant effects of 2D pores on mechanical behaviors of plasma sprayed ceramic coatings during thermal exposure. Issue 5 (1st April 2020) - Wang, Li-Shuang; Tang, Chun-Hua; Dong, Hui; Li, Guang-Rong; Yang, Guan-Jun
Abstract: Realizing engineering application of new candidate ceramic materials is highly required for the development of advanced thermal barrier coatings (TBCs). In addition to the optimization of intrinsic properties of ceramic materials, a feasible way is to tailor the structure of coatings based on the understanding of structure-properties evolution during thermal exposure. Herein, the unique sintering behavior and the consequent effect on spallation of plasma sprayed coatings made of a candidate material, i.e., La2 Zr2 O7 (LZO), were investigated by experiments and simulation. Experimental results showed that significant changes occurred for the porosity, 2D pore density and hardness during thermal exposure. The 2D pores are the essential microstructural characteristics and are dominantly responsible for the changes of mechanical property. Simulation results suggested that the healing of 2D pores increase the driving force for crack extension. This is the main cause for the spallation of ceramic top coat during thermal cyclic test. Finally, some structural designs towards long lifetime of TBCs were discussed. The dominant effects of 2D pores on mechanical properties and failure of TBCs provide fundamental understanding to the structural tailoring of advanced TBCs for future applications.